Levantamento nutricional de bananais do vale do ribeira-sp pela análise foliar - De Godoy, Leandro José Grava [UNESP]; Gomes, Juliana Macedo [UNESP]; De Mendonça, José Carlos (My University, 2011)
The region of the Vale do Ribeira, SP is responsible for 70% of banana production in the state of São Paulo. The cultivation of bananas plants requires large amounts of nutrients for proper development. The survey of the leaf nutrient concentration of crops aims to identify the nutrients deficiencies and excesses, and to direct regional fertilization researches to be planned. The objective of the work was to survey the nutritional status of banana crop in Vale do Ribeira, SP. We used results of nutrient leaf analysis of and Prata and Cavendish subgroups cultivars of samples collected in banana crops representatives in Vale do Ribeira, in the period 1998 to 2005. The leaf samples were collected in banana crops of the following counties: Cajati, Eldorado, Jacupiranga, Pariquera-Acu, Registro and Sete Barras. Were determined the leaf concentration of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn. Most banana crops sampled showed deficiency of N and S. The deficiency of K observed in some banana crops must be due to the imbalance cation (K: Mg: Ca). The B was found in the nutrient excess more frequently. The average leaf content of K, Ca, S, Cu and Zn was higher in Prata subgroup than in the Cavendish subgroup.
Nutritional survey of banana crops of the vale do ribeira-sp by the foliar analysis
Keywords: Banana; Foliar analysis; Musa sp